English Teachers’ Perceptions and Practices of Differentiated Instruction (DI) in the Merdeka Curriculum - Mutmainah, Mutmainah; Sundari, Hanna; Juhana, Juhana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research project investigated the use of DI by teachers and confirmed their practices to learn more about teachers' perceptions using a qualitative approach. Four research instruments were used to collect data in this investigation: document analyses, classroom observations, questionnaires, and interviews. Document analyses and classroom observations were employed to obtain data concerning teachers' actual practices of DI. In the meantime, a questionnaire has been used to obtain data on teachers' perceptions and practices regarding DI. Finally, interviews have also been conducted to determine teachers' perceptions of DI. The result of the study revealed that the participants exhibited high proficiency in using DI strategies in their classrooms. The assessment considered various dimensions, including understanding DI concepts and objectives, adapting instruction to diverse student needs, evaluating students through diagnostic assessments, and aligning teaching strategies with individual learning profiles. However, there was room for improvement, especially in tailoring instruction based on diverse learning profiles. Furthermore, the English teachers' perceptions of DI significantly shaped their instructional practices. While there was a solid theoretical understanding and commitment to personalized instruction, practical challenges and systemic constraints impacted the seamless integration of DI principles. The teachers' commitment to addressing these challenges, demonstrated through varied instructional practices, underscored the dynamic interplay between perceptions and the complex reality of implementing DI in the classroom. Keywords: English Teacher, Differentiated Instruction (DI), Merdeka Curriculum, Perceptions and Practices